2015
DOI: 10.1093/molbev/msv181
|View full text |Cite
|
Sign up to set email alerts
|

A Common Genetic Origin for Early Farmers from Mediterranean Cardial and Central European LBK Cultures

Abstract: The spread of farming out of the Balkans and into the rest of Europe followed two distinct routes: An initial expansion represented by the Impressa and Cardial traditions, which followed the Northern Mediterranean coastline; and another expansion represented by the LBK (Linearbandkeramik) tradition, which followed the Danube River into Central Europe. Although genomic data now exist from samples representing the second migration, such data have yet to be successfully generated from the initial Mediterranean mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
133
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 154 publications
(150 citation statements)
references
References 59 publications
15
133
0
2
Order By: Relevance
“…The best explanation for this observation is that migration to southwestern Europe started in the Aegean but was independent from the movement to Germany via Hungary. This is also supported by other genetic inferences (24) and archaeological evidence (33). An alternative scenario is a very rapid colonization along a single route with subsequent gene flow back to Greece from Spain.…”
Section: Functional Variationsupporting
confidence: 86%
“…The best explanation for this observation is that migration to southwestern Europe started in the Aegean but was independent from the movement to Germany via Hungary. This is also supported by other genetic inferences (24) and archaeological evidence (33). An alternative scenario is a very rapid colonization along a single route with subsequent gene flow back to Greece from Spain.…”
Section: Functional Variationsupporting
confidence: 86%
“…Recent aDNA studies have shown that early farmers in central and southwestern Europe show a genetic affinity to populations in the Near East, with the implication that demographic expansion and migration played an important role in the appearance of the Neolithic in these regions, although an admixture with local foragers is also indicated (e.g. Haak et al 2010;Olalde et al 2015). Palaeogenetic research into the transition in the British Isles is less advanced and archaeological opinion is still divided over whether colonisation from mainland Europe (Sheridan 2010) or indigenous adoption (Thomas 2008) was the main driver of Neolithization.…”
Section: Introductionmentioning
confidence: 99%
“…145 We also generated 62 new direct radiocarbon dates (Extended Data Bronze Age Britain. We combined our data with previously published ancient DNA data [2][3][4][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] 150 to form a genome-wide dataset of 476 ancient individuals (Supplementary Table 1). The 151 combined dataset included Beaker-associated individuals from Iberia (n=20), southern France 152 (n=4), northern Italy (n=1), central Europe (n=56), The Netherlands (n=9) and Britain (n=19).…”
mentioning
confidence: 99%